A Survey On Load Balancing Methods and Algorithms in Cloud Computing - Lagwal, M; Bhardwaj, N (International Journal of Computer Sciences and Engineering, 2025)
the IT trade has played a noteworthy role in computing. Due to this increasing of demands day by day the need of computing and storage is increasing quickly. Client-Users are demanding for services and resources at any time are provided. For this cloud computing requires load balancing techniques to control and handle overloaded demand and requires. Load balancing is one of techniques to control lots of requires at a time and help to utilization of resource and services. In load balancing various algorithm are provide to the user for satisfaction. In this paper, we have done the review of some load balancing algorithms based on different parameters in cloud computing.